Wpływ Nieliniowej Charakterystyki Tłumienia Tarciem Wewnętrznym na Drgania Wymuszone - Osiński, Z. (Engineering Transactions, 1959)
The author sets out to find a method of a appraisal of a damping characteristic considered to be non-linear. For this purpose, he assumes that the damping is a non-linear function of velocity, the relation in question being: R(v) = av + Bv3. Next, examination is made of the influence of such a non-linear damping on the forced vibration of a system with one degree of freedom, and linear elastic characteristics provoked by a sinusoidal external force. The differential equation of motion is solved by approximate means constituting a generalization of the small parameter method. This generalization consits is asssuming that only the non-linear part of damping is small, an assumption not made in relation to the linear part of damping and the external force. The influence of non-linearity of damping on the vibration amplitude D, the energy dispersed E, and the mean power N, of the external force, are examined in the case of basic resonance. It is found that the ratios D/q, E/q2, N/q2 are influenced by the amplitude of the external force q. This leads the author to the conclusion that the non-linearity of damping characteristic can be detected by examining the influence on the vibration of the amplitude of the external force.